Does ESG disclosure enhance firm performance during COVID-19? Evidence from Nifty 500 firms - G. Vidya Bai; Daniel Frank; K. Sudhir Prabhu (Investment Management & Financial Innovations)
Market turmoil caused by COVID-19 has weakened firms’ financial performance, highlighting the prominence of sustainable business practices by incorporating Environmental, Social, and Governance performance and their disclosure. Though past studies investigated COVID-19’s impact on firm performance, there is consensus on the role of firms’ Environmental, Social, and Governance disclosures between firm performance and the pandemic. With this view, the study aims to examine the impact of COVID-19 on firms’ financial performance with the moderating role of Environmental, Social, and Governance performance disclosure. To do so, the study retrieved data of Nifty 500 index companies from the Bloomberg database for a sample period ranging from 2016 to 2022. To this end, the study performed the fixed-effect regression and GMM model. The findings reveal a significant negative impact of the pandemic on Return on Assets (β =-4.812), Return on Equity (β =–.675), and Earnings Per Share (β = –2.875), highlighting the unfavorable effect of the pandemic on firm performance. Further results showed that firms’ Environmental, Social, and Governance performance disclosure positively moderates the connection between COVID-19 and Return on Assets (β = 3.231), Return on Equity (β = 0.032), and Earnings Per Share (β = 1.523), respectively. This indicates that companies actively involved in Environmental, Social, and Governance disclosure are less likely to suffer during the pandemic in terms of financial performance due to their ESG disclosures.